Cytotoxic diterpenoids from Salvia glutinosa and comparison with the tanshinone profile of danshen (Salvia miltiorrhiza) - Ayvazyan, Arpine; Deutsch, Lenard; Zidorn, Christian; Kircher, Brigitte; Çiçek, Serhat S. (Frontiers in Plant Science, 2023)
The roots of Salvia miltiorrhiza are the source of the traditional Chinese medicine danshen and the class of tanshinones, particular quinoid nor-diterpenoids of the abietane type. Of these compounds, cryptotanshinone, dihydrotanshinone I, tanshinone I, and tanshinone IIA, have been extensively studied for their anticancer potential, not only but as well because of their high abundance in S. miltiorrhiza and their thus easy availability. However, also additional Salvia species are known to contain tanshinones, mainly such of the subgenus Glutinaria, of which S. glutinosa is the only species widely occurring in Europe. Using UHPLC-DAD-MS, the tanshinone profile of S. glutinosa roots collected from two different locations was compared to the profile in S. miltiorrhiza roots. In addition, tanshinone IIA and another six diterpenoids from S. glutinosa were investigated for their antiproliferative and cytotoxic potential against MDA-MB-231 and HL-60 cells. Apart from dihydrotanshinone I, which has been previously characterized due to its anticancer properties, we determined danshenol A as a highly antiproliferative and cytotoxic agent, significantly surpassing the effects of dihydrotanshinone I. With regard to the diterpenoid profile, S. miltiorrhiza showed a higher concentration for most of the tanshinones, except for (+)-danshexinkun A, which was present in comparable amounts in both species. Danshenol A, in contrast, was only present in S. glutinosa as were dehydroabietic acid and (+)-pisiferic acid. The results of our study underlines the long traditional use of danshen due to its high amount on tanshinones, but also demonstrates the potential value of investigating closely related species for the discovery of new biologically active lead compounds.